From harassing courtship to online breaking up, cyber violence in high school - Velázquez Reyes, Luz María (2020)
This paper’s objective is to document the incidence and experience with cyber violence faced by 295 students (60% female and 40% male) from an urban university high school in the Valle de Toluca, Mexico. Based on a mixed research design, the self-report "Online Violence, 2019", a Likert-type questionnaire with 19 statements has been applied. In addition to a narrative-generating question, the students were questioned about their experience with online violence. Among the results, it stands out that 34.23% of the students have fallen in love through the internet, in addition, they face a high incidence of virtual grievances around romantic relationships, on average, 58.71%, have suffered cyber violence, 40.56% have perpetrated and 84.06% have observed it. Specifically, 81% have suffered harassing courtship, 62.71% have been sentimentally "finished" through a message and 32.54% have suffered excessive control from their ex-partner or current partner. The student narrative reveals that the girls are mostly victims in online breaking but more perpetrators of obsessive control through the cell phone.